Exploring the development of an integrated, participative, water quality management process for the Crocodile River catchment, focusing on the sugar industry - Sahula, Asiphe (Rhodes University, Faculty of Science, Institute for Water Research, 2015)
Water quality deterioration is reaching crisis proportions in South Africa. Many South African catchments are over-allocated, and decreasing volumes of source water mean increasing concentrations of pollutants. The Crocodile River Catchment in the Mpumalanga province in South Africa was identified through previous research, as a catchment faced with deteriorating source water quality for water users in the catchment. Poor source water quality has become a sufficiently acute concern for the stakeholders in this catchment to co-operate in developing a process that assists with compliance control of their water use and waste disposal to reduce costs, decrease industrial risks as water quality compliance increases, and improve source water quality. The sugar industry is downstream within the Crocodile River Catchment, and is affected by the activities of all upstream water users; the industry is thus dependent on the stakeholders upstream participating in the effective management of the resource. However, the sugar industry is also located just before the confluence of the Crocodile River and Komati River upstream of the Mozambique border, and thus the water quality of the sugar industry effluent will affect the quality of the water that flows into Mozambique. The sugar industry is on the opposite river bank to the Kruger National Park, which has high water resource protection goals. Therefore, the sugar industry has a national role to play in the management of water resources in the Crocodile River Catchment. This study provides a focused view of the role of the sugar industry in the development of a co-operative, integrated water quality management process (IWQMP) in the Crocodile River Catchment. In order to address the objectives of this study, this research drew from an understanding of the social processes that influence water management practices within the sugar industry as well as social processes that influence the role of the Inkomati-Usuthu Catchment Management Agency as the main governing institution in water resource management in the Inkomati Water Management Area. The study also drew from an understanding of scientific knowledge in terms of a water chemistry which describes the upstream and downstream water quality impacts related to the sugar industry. The water quality analysis for the Lower Crocodile River Catchment shows a decline in water quality in terms of Total Dissolved Solids (TDS) loads when moving from below Mbombela to the Mozambique border. The major sources of TDS in the Lower Crocodile River are point source dominated, which may be attributed to the extensive mining, industrial and municipal activities that occur across the catchment. When observing Total Alkalinity (TAL) and pH values from below Mbombela to the furthest monitoring point, there is deterioration in the quality of the water in the Lower Crocodile River, with the Kaap River contributing a negative effect that is diluted by the Crocodile main stem. The Hectorspruit Waste Water Treatment Works (WWTWs) (located in the Lower Crocodile River Catchment) contributes high concentrations of TDS and TAL into the Crocodile River. Total Inorganic Nitrogen and Soluble Reactive Phosphorus concentrations decrease in the lower reaches of the Crocodile River compared with the river below Mbombela, which can be attributed to the extensive sugar cane plantations located in the Lower Crocodile River Catchment acting as an "agricultural wetland" that serves a function of bioremediation resulting in large scale absorption of nutrients. This is an interesting result as earlier assumptions were that fertiliser application would result in an overall increase in nutrient loads and concentrations. Biomonitoring data show no substantial change in aquatic health in the LowerCrocodile River Catchment. For a catchment that has an extensive agricultural land use in terms of sugarcane and citrus production, the Crocodile River is unexpectedly not in a toxic state in terms of aquatic health. This is a positive result and it suggests that pesticide use is strictly controlled in the sugar and citrus industry in the Crocodile River Catchment. For long term sustainability, it is essential for the sugar industry to maintain (and possibly improve) this pesticide management. The social component of this study aimed to provide an analysis of the management practices of the sugar mill as well as examining agricultural practices in the sugar cane fields in relation to water quality management through the use of Cultural Historical Activity System Theory (CHAT). This component showed that there are contradictions within the sugar industry activity system that are considered to be areas of "tension" that can be loosened or focused on to improve the contribution the sugar industry can make to the IWQMP. Surfacing contradictions within the sugar industry activity system and the Inkomati-Usuthu Catchment Management Agency activity systems highlighted areas of potential for learning and change. While an understanding of biophysical processes through scientific knowledge is critical in water management decision making, it is evident that an understanding of other actors, institutions and networks that inform water quality management decision-making also plays a significant role. The notion of improving the role of scientific or biophysical knowledge in contributing to socio-ecologically robust knowledge co-creation, decisions and actions towards resolving water quality problems is emphasised. Specifically, moving towards improving interactions between scientists and other actors (water users in the Crocodile Catchment in this case), so that scientific practices become more orientated towards societal platforms where water quality management is tackled to enable improved water quality management practices. Therefore, linking the social and biophysical components in this study provides a holistic understanding of how the sugar industry can contribute to the development of an IWQMP for the Crocodile River catchment.
Keywords: Water quality management -- South Africa -- Krokodilrivier (Mpumalanga); Watersheds -- South Africa -- Krokodilrivier (Mpumalanga); Integrated water development -- South Africa -- Krokodilrivier (Mpumalanga); Water quality management -- Social aspects -- South Africa -- Krokodilrivier (Mpumalanga); Social responsibility of business -- South Africa -- Krokodilrivier (Mpumalanga); Water quality -- South Africa -- Krokodilrivier (Mpumalanga)